Teaching Medical Informatics: Teaching on the Seams of Disciplines, Cultures, Traditions - Möhr, J. R. (Methods of Information in Medicine, 1989)
This paper reviews different concepts of medical informatics and identifies two families of approaches to education in it: a “specialist” approach, whereby medical informatics is taught as a specialization track for established disciplines like medicine, computer science, nursing, engineering, etc., and a “generalistic” approach, whereby it is taught as an integrated discipline incorporating essential traits of the aforementioned disciplines. The pros and cons of these approaches are outlined. The need to accommodate specific requirements of education is emphasized and these are identified, together with an outline of particular challenges that we are facing.
Keywords: Medical Informatics; Computing Milieu; Education; Curriculum; Health Specialties